Laws Passed in the Territory of the United States North-West of the River Ohio 37-38 (1792) - (:unkn) unknown (My University, 1791)
An Act . . . To prevent the selling or pawning of arms, ammunition, cloathing, and accoutrements, Chapter XII, Sec. 2: Prohibited the purchase of public arms, ammunition, clothing, or accoutrements pertaining to non-commissioned officers or private soldiers in service. Violators shall be fined the value and costs of the articles on the first violation. Proceeding violators shall pay fines and costs of articles and shall suffer imprisonment not exceeding one month.
Keywords: MILITIAS